The role of work–family conflict in the association between long working hours and workers’ sleep disturbance and burnout: results from the sixth Korean Working Conditions Survey - Seong-Uk Baek; Jong-Uk Won; Jin-Ha Yoon (BJPsych Open, 2023)
Background The effect of long working hours on mental health has drawn great social attention in recent years.